ChemInform Abstract: Experimental Investigation of Phase Equilibria in the Sn—V—Zn System at 450 °C and 600 °C. Issue 30 (4th July 2013) - Wu, Changjun; Su, Xuping; Liu, Ya; Peng, Haoping; Wang, Jianhua; Tu, Hao
Abstract A series of alloys of the title system is prepared by melting (corundum crucible in evacuated quartz tube, 1000 °C, 10 h, bottom quenching to minimize Zn loss, annealing at 450 °C or 600 °C, 15—20 d) or powder metallurgical cold pressing followed by annealing (450 °C, 30 d, or 600 °C, 15 d) and quenching.